AN ASSESSMENT OF THE EFFECTS OF ALCOHOLISM ON DRUNKARDS IN KEFFI LOCAL GOVERNMENT AREA OF NASARAWA STATE, NIGERIA: ISLAMIC PERSPECTIVE - Sulaiman, Abdullahi Adamu (European Scientific Journal, ESJ, 2013)
The paper embarks on the assessment of the effects of alcoholism on drunkards in Keffi Local Government Area of Nasarawa State, Nigeria using Islamic perspective. The objectives are to identify the perception, extent of consumption and effect of alcoholic consumption among drunkards in Keffi LGA, Nasarawa State, Nigeria. The paper adopted survey method of research and surveillance technique was used for sample size determination. Structured questionnaire was distributed to 200 sampled respondents across Keffi Local Government Area and descriptive statistics was used for data analysis. The research found wide spread negative perception about alcohol among the people of Keffi and concluded that alcohol consumption has had profound negative effects on both the individual drunkards, the family (especially the children and women) and recommends that all other sources of law should emulate the Islamic concept of total abstinence on alcoholic beverages.